"Lapse of Happily": Consuming Everyday Banality in American Experimental Poetry - Siltanen Elina (Brill, 2022)
Robert Fitterman’s Sprawl and Claudia Rankine’s Don’t Let Me Be Lonely take a conceptualizing approach toward everyday life and ordinary, banal language. Sprawl consists mainly of recycled material, specifically online reviews of stores that are typical in an American mall. Rankine’s book contains, along with personally reflective passages of text, appropriated lists, quotations and pictures. Both books comment on staple, banal aspects of contemporary Western everyday life, such as the availability of a large number of choices and the desire to seek temporary satisfaction through consumption. In this chapter, I argue that the writing of Fitterman and Rankine proposes ways of acknowledging, but not necessarily revivifying, the contingent relations between happiness and sadness, or satisfaction and dissatisfaction, within the ordinariness of the everyday.
Thinking with the Familiar in Contemporary Literature and Culture 'Out of the Ordinary'